Languages in space - Mildner, Vesna (Array, 2002)
The activation-orienting hypothesis and possible effects of hemispace for verbal stimuli in the native (Croatian) and foreign (English) language were studied on a sample of 72 healthy female right-handers. In an experimental design involving two competing commands referring to objects in left and right hemispace presented simultaneously to the two ears it was recorded which of the two was attended to first. The activation-orienting hypothesis was confirmed for Croatian but not for English. Clear dissociation between the two languages was found with respect to preferred hemispace: for the stimuli in the native language the subjects preferred the left hemispace, whereas for the stimuli in the foreign language they preferred the right hemispace.